SANDHYA KALANING BUDAYA SUBAK (PERSPEKTIF TRI HITA KARANA) - I Wayan Sudika (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
The existence of subak in Bali has been very well known to foreign countries, even one of the subaks in Tabanan, namely the Jatiluwih Subak, designated as the World Cultural Heritage (WDB). But behind subak's fame, there is a lot of land use change that causes the subak area to narrow from year to year. In addition, the interest of the young generation to become rice farmers is very small, they prefer to work in the service sector, which provides a more certain income. This caused most of the subak manners to be classified as old. The small interest of the young generation to become rice farmers, followed by the decreasing implementation of tradition / culture carried out by subak manners seen from the tri hita karana aspect. In the aspect of parhyangan, most of the subak traditions / cultures are rarely carried out and instead are no longer implemented. In the Pawongan aspect, today there is almost no more working relationship between subak manners based on mutual cooperation and mutual assistance, only laborbased relations, measured by the value of money. Likewise in the aspect of Palemahan, most of the traditions / cultures that were formerly carried out, are now no longer implemented.Keyword : Subak, Culture dan Tri Hita Karana